The Association between Family Functioning and Aggressive Behaviors in Adolescents by the Role of Parental Mental Health as a Mediator - Navari, Sahar; Foroughi kaldareh, Zahra (Shahroud Journal of Medical Sciences, 2024)
Background: Adolescents often experience changes in their hormones, psychology, and social environment, which can lead to the development of aggressive behaviors. This study aimed to examine how family dynamics are related to the aggressive behavior displayed by adolescents, with a particular focus on the role of parents' mental health as a mediating factor.Methods: In this descriptive-correlation study, the Path analysis was conducted to determine the associations of research variables. The statistical population included all female students of junior and senior high schools in Rasht in the 2017–18 academic year. The stratified cluster sampling method was adopted to select 350 high school students. The research measurement tools included the Aggression Questionnaire, Family Assessment Device (FAD), and General Health Questionnaire–28 (GHQ-28). The data was analyzed using the SPSS version 27 software and the Smart PLS3 software as well as the structural equation modeling method. The significant level was set at 0.05.Results: According to the research findings, all the Path coefficients in the research model were statistically significant. The results indicated that family performance had a negative and significant impact on aggression (β=-0.162, Pvalue<0.001), anxiety (β=-0.955, Pvalue<0.001), and depression (β=-0.904, Pvalue<0.001). Moreover, the family performance had a positive and significant effect on physical health (β=0.78, Pvalue<0.001) and social function (β=0.886, Pvalue<0.001), Physical health (β=-0.348, Pvalue<0.001) and social function (β=-0.073, Pvalue=0.024) also had a negative and significant impact on aggression as mediating variables. Additionally, anxiety (β=0.351, Pvalue<0.001) and depression (β=0.09, Pvalue=0.024) as mediating variables had a positive and significant effect on aggression.Conclusions: Consequently, achievement motivation had a mediating role in associations of academic engagement with academic self-concept and academic support in gifted students. The findings can be used as an appropriate model for designing and developing certain programs to improve academic engagement and enhance the academic motivation of students.The findings of the current research demonstrated the impact of cognitive.